Мethods for Revealing Incomplete Topical Fragments of Pedagogical Knowledge - Andrey V. Korzhuyev; Aleksandra S. Sokolova (National Research Mordova State University, 2017)
Introduction: the process of "motion" of pedagogy to "gnoseologic ideal" implies the necessity of systema-tisation of theoretic and practical results produced in scientific community and revealing those scientific fragments which are not completed yet. It is mostly important for experienced researchers as well as beginners to be orientated in the field of pedagogic problems to determine problems topical for modern research. The purpose of the article is to discover and present "mechanisms" which give to pedagogical researchers the possibility to find fragments of knowledge requiring content revamping, detailing, reworking and thus furthering. Materials and Methods: content analysis and logical interpretation of philosophic and pedagogic texts, analysis of results of educational practice, analysis of specifics of methodological principles application in pedagogic theory and practice; hypotheses and their theoretic interpretation; theoretical expanding of results obtained, heuristic synthesis and reflection of the results obtained. The conception of completion of scientific knowledge developed by R. Descartes and M. Montaigne including presentation of the process of increasing volume of knowledge accompanied by the same volume of unknowledge is the methodologic foundation of our research. Results: "white spots" of modern pedagogical theory and practice are discussed in the article; the attention is focused on the methods used by researches to find out pedagogical problems which are not completed yet and on the role of those fragments in pedagogic development. The readers' attention is mainly focused on application of symmetric principal in pedagogical knowledge and research. Classification including 3 types of "mechanisms" of finding topical fragments of noncomplete kno wledge is presented - this classification may be used by researches choosing field and topic of topical r esearch. Discussion and Conclusions: the fragment of theoretical pedagogy "knowledge about unknowledge" is presented as a form of scientific and methodologic reflection; the attempt to find theoretical foundation of methods discovering "white spots" in pedagogy is described; the role of "white spots" in the process of pedagogical scientific development is discussed. Main conclusion is presented by thesis "increase of volume of knowledge is accompanied by correlated volume of unknowledge" which was confirmed by analysis of pedagogic development. The process of revealing incomplete pedagogical fragments is principally structurable and classifiable; noncompletion of classification given in the article presents a direction for perspective pedagogic research.